2018
DOI: 10.31011/reaid-2018-v.86-n.24-art.96
|View full text |Cite
|
Sign up to set email alerts
|

Análise do Comportamento Sexual de Adolescentes e Fatores de Risco à Saúde

Abstract: Objetivou-se analisar o diagnóstico comportamental de adolescentes de uma escola pública por meio do modelo PrecedeProceed. Estudo de abordagem qualitativa do tipo pesquisa-ação participativa em saúde (PaPs), desenvolvida comadolescentes, alunos de uma escola pública do município de Paraíba do Sul-RJ. As técnicas de coleta de dados foramaplicação de um questionário com perguntas fechadas e uma dinâmica interativa denominada World Café ou Café Mundial.Os dados do questionário são apresentados por meios de estat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Female participants obtained a higher average of success regarding knowledge and practices tangent to HIV, which agrees with the existing literature where it is observed that men are more vulnerable about the risks regarding STIs in relation to women, since they have their first relationship earlier (Scoralick et al, 2018). Still aware of the fact that, in a casual way, girls discuss sexuality with friends and new acquaintances and choose a stable partner or boyfriend to perform the first sexual intercourse (Oliveira et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Female participants obtained a higher average of success regarding knowledge and practices tangent to HIV, which agrees with the existing literature where it is observed that men are more vulnerable about the risks regarding STIs in relation to women, since they have their first relationship earlier (Scoralick et al, 2018). Still aware of the fact that, in a casual way, girls discuss sexuality with friends and new acquaintances and choose a stable partner or boyfriend to perform the first sexual intercourse (Oliveira et al, 2018).…”
Section: Discussionsupporting
confidence: 90%